UMPSA highlights innovation and builds global bridges at Expo 2025 Osaka - Nur Ezzati, Mohd Nasir (UMPSA, 2025)
OSAKA, JAPAN, 21 July 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) marked another significant milestone in its globalisation journey by participating in Expo 2025 Osaka, held at Yumeshima Island, Japan. Coordinated by the Ministry of Higher Education (MOHE), Malaysia’s official delegation to this world expo aligns with the nation’s aspiration to elevate education diplomacy, sustainability, and innovation on the global stage.